Factors that Motivate Tourists’ in Visiting the Cultural Festivals: A Study - Nongsiej, Prosperous; Mothilal, Lakavath (Turizam, 2019)
Festivals is a fast-growing tourism segments, which is consider as an importance tool for promoting and understanding market segmentation based on tourists motivation. Identifying tourist’s motivation has been a key requirement which leads to tourism development and improvement, it also facilitate marketers, stakeholders and decision makers to formulate efficient marketing strategies, improve and enhance the satisfaction and leisure of the tourists throughout the festivals.The main purpose of the study is to identify the factors that attract tourists visiting Meghalaya to attend the various cultural festivals, Eighteen festival motivation variables were formed based on various literatures and reduced to three dimensions by Factor analysis. Also these motivational factors were examine to confirm if there is any statistical significant between the demographic variables by using ANOVA and T-Test. The results indicate that “Change from everyday life” and “Friends and family togetherness” are the most important factors for tourist visiting the cultural festivals in Meghalaya.
Keywords: Festivals; cultural; Meghalaya; tourists; motivation